2018
DOI: 10.1002/2017jg004249
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Organic Matter Composition in Stream Runoff Following Large Storms: Role of POM Sources, Particle Size, and Event Characteristics

Abstract: Large storm events possess significant erosive energy capable of mobilizing large amounts of sediment and particulate organic matter (POM) into fluvial systems. This study investigated how stream POM composition varied as a function of the watershed POM source, particle size, storm event magnitude, and seasonal timing. POM composition was characterized for multiple watershed sources and for stream POM following storms in a second‐order forested stream. Carbon (C) and nitrogen (N) amount, C:N ratio and isotopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 48 publications
(74 reference statements)
0
29
0
Order By: Relevance
“…Storm suspended sediments for fingerprinting were collected from the upstream and downstream sampling sites (Figure 1) using passive samplers. These samplers were modified from Phillips et al (2000) and Johnson et al (2017) and were designed to collect a composite sample of sediment over the duration of an event. The samplers were constructed from 4 in.…”
Section: Methodsmentioning
confidence: 99%
“…Storm suspended sediments for fingerprinting were collected from the upstream and downstream sampling sites (Figure 1) using passive samplers. These samplers were modified from Phillips et al (2000) and Johnson et al (2017) and were designed to collect a composite sample of sediment over the duration of an event. The samplers were constructed from 4 in.…”
Section: Methodsmentioning
confidence: 99%
“…A nonlinear least squares optimization of the bucket model (per observations from the leachate trays) resulted in an S max of 19.9 mm (figure S3 in supplemental materials). Although litter leachate trays are commonly deployed in forest ecohydrological research (e.g., Campbell et al 2007, Johnson et al 2018, we note that flow pathways through natural litter deposits may be more efficient, explaining why the modelling exercise yielded higher storage estimates. These water storage capacity estimates exceed all forest litter storage values that have been estimated to date (ranging from 0.2-8.0 mm (Gerrits and Savenije 2011).…”
Section: Resultsmentioning
confidence: 87%
“…Similarly, the study of Johnson et al (2017) in a forested catchment in the Piedmont region, Maryland (USA) showed that sediment sources from forest floor litter had the highest TC and TN concentrations compared to near-stream sources such as stream bed and stream banks. The fresher material from the forest floor was likely the least degraded resulting in higher C and nutrient concentrations (Johnson et al, 2018). Old growth forests maintain a tight nutrient cycle through high and diverse aboveground biomass.…”
Section: Land Use Affects Sediment-associated Carbon and Nutrients Concentrationsmentioning
confidence: 99%
“…Sediments and their associated organic C and nutrients, such as N and P (Horowitz, 2008;Johnson et al, 2018;Quinton et al, 2001) may impact streams by reducing benthic communities, primary productivity and water storage capacity of water reservoirs (Hunink and Droogers, 2011;Tamene et al, 2006) and by increasing turbidity (Stenfert Kroese et al, 2020b;Tamooh et al, 2014). In nutrient-limited freshwater systems, an excess of nutrients can cause eutrophication (Jarvie et al, 2019;Smith et al, 2017;Smith and Schindler, 2009), inducing algal blooms and promoting invasive weeds (e.g.…”
Section: Introductionmentioning
confidence: 99%